Ovarian hemangioma: rare case report and review of literature - Pawar, Amol P.; Garude, Swapnali G.; Patwardhan, Leena M.; Solanki, Vrushti P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian haemangiomas are vascular tumours arising from ovary of female genital tract, are very rare. Not more than 60 well-documented cases of ovarian haemangioma are noted. Authors reports 77-year-old woman presented with pain in lower abdomen and discomfort along with bloating sensation since 1 month in gynaecology outpatient department (OPD) at Nowrosjee Wadia Maternity Hospital on august 2023. Ultrasonography suggestive of large cystic mass is seen the left hemi pelvis measuring 7.0×5.4 cm with multiple calcifications. Multidetector computed tomography (MDCT) suggestive of about 8×7.5×6 cm well-defined cystic lesion with multiple thick septae with calcification within it seen in left adnexa likely to be teratoma. Patient was posted for exploratory laparotomy. Total abdominal hysterectomy with bilateral salphingoopherectomy with partial dissection of retroperitoneal mass was done. Histopathology report suggested microscopic examination as ovarian tissue is replaced by variably sized thick and thin vascular channels and blood vessels. These vascular channels have partially denuded endothelial lining. The vascular channels are filled with frank haemorrhage suggestive of ovarian haemangioma. Ovarian haemangiomas sometimes coexist with genital tract diseases or even malignancies and thus ovarian haemangioma can be clinically significant.